A method for the preparation of a composite carbon filler for rubber compositions
Patent Information
- Application Number
- CN202611292599.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-25
- Publication Date
- 2026-10-09
AI Technical Summary
[0011]针对背景技术中提到的现有复合碳填料制备方法中存在的碳纳米管与炭黑分散不均、无法通过计算直接确定最优配比、需依赖成本高昂的试错法逐一筛选组分等问题,本发明提供一种用于橡胶组合物的复合碳填料的制备方法
(1)精准确定最优配比,消除试错依赖。 本发明通过公式(I)和公式(II)实现了碳纳米管与烃原料投入比以及复合碳填料在橡胶组合物中用量的精确计算。无论对于何种橡胶牌号,只需将其物性参数代入公式,即可直接获得最优配比,无需进行大量配比筛选试验,显著降低了研发成本和时间消耗。
Smart Images

Figure CN122878629A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the technical field of fillers for the rubber industry, specifically relating to a method for preparing a composite carbon filler for rubber compositions, and more particularly to a method for preparing an in-situ composite filler of carbon nanotubes and carbon black. Background Technology
[0002] Since their discovery, carbon nanotubes (CNTs) have been considered an ideal choice for reinforcing rubber fillers due to their excellent mechanical, electrical, and thermal properties. Combining CNTs with traditional carbon black (CB) fillers is expected to leverage their synergistic reinforcing effect, significantly improving the overall performance of rubber compositions. However, the large specific surface area and high surface energy of carbon nanotubes make them highly prone to aggregation. Achieving uniform dispersion of carbon nanotubes in the rubber matrix and determining the optimal ratio of carbon nanotubes to carbon black remain two core challenges in this field.
[0003] Prior art, such as a method for preparing a composite carbon filler, can be found in US Patent Application No. US2019322818 (A1); IPC C01B 32 / 05; C01B 32 / 152; C01B 32 / 168; C01B 32 / 174; C08J 3 / 20; C08J 3 / 22; C08K 3 / 04; C08K 5 / 03; C09C 1 / 44; C09C 1 / 46; C09C 1 / 48; C09D 123 / 16; Publication date: October 24, 2019. The preparation steps of this composite carbon filler include: a) Dispersing carbon nanotubes in a liquid medium; b) Mix the resulting dispersion with solid particles such as carbon black; c) Dry the prepared mixture to remove liquid.
[0004] The resulting composite carbon filler contains carbon nanotubes at a mass percentage of 1%, 5%, 7% to approximately 20%, 30%, or 50%. This ultimately yields a mixture of nanostructures and particles, such as a mixture of carbon nanotubes and carbon black. This method can produce particles coated with carbon nanotubes, or particles coated with other carbon nanostructure materials, to form a premix. The resulting mixture can be further dispersed in a polymer matrix, such as an elastomer matrix. According to the invention, the content of carbon nanotubes or other carbon nanostructure materials in the elastomer composition can be from 0.5 wt%, 1 wt%, or 2 wt% to 2 wt%, 3 wt%, 4 wt%, or 5 wt% by mass. Depending on the size and amount of the carbon nanotubes and carrier particles, a carbon nanotube network structure can be formed, rather than a structure where the particles are coated with carbon nanotubes.
[0005] The reason it failed to achieve the expected technical effect is that without first employing a costly trial-and-error method to screen all possible proportions of the components, it is impossible to obtain the optimal composite carbon filler composition. Similarly, determining the optimal content of the composite carbon filler in the rubber composition presents the same challenge and still requires component proportion screening experiments. Screening the optimal amount of composite carbon filler added to the rubber composition also presents difficulties, and this screening process also requires repeated adjustments to the component proportions through trial and error.
[0006] Existing technology, such as a method for preparing a composite carbon filler composed of carbon nanotubes and solid particles such as carbon black, graphite particles, or glassy carbon, is described in patent EP4286465, IPC C08K3 / 04, authorized on 2023-12-06. This method involves wet mixing carbon nanotubes with solid particles in a desired liquid. Mixing can be performed using any suitable batch or continuous mixer. The mixture can then be dried using any suitable drying equipment. The prepared mixture can be added to a polymer or elastomer composition according to known polymer, rubber, and elastomer compounding methods.
[0007] The reason why the expected technical effect could not be achieved is that a sufficiently uniform mixture of carbon nanotubes and carbon black could not be obtained. This is because when carbon nanotube aggregates are mixed with solid particles such as carbon black, graphite particles or glassy carbon, they do not disperse but are instead compacted and their volume decreases. This effect prevents the performance of the prepared rubber composition from being significantly improved.
[0008] The prototype utilizes an in-situ preparation method for a super-strong composite filler of carbon nanotubes and carbon black, as described in patent CN108047495B, IPC C08K 7 / 24; C08K 3 / 04; C08L 7 / 00; C08L 23 / 06; authorized announcement date: 2020.03.10. According to the prototype, carbon nanotubes are first incorporated into the liquid raw material for preparing carbon black, with a mass ratio of carbon nanotubes to liquid raw material ranging from 0.1:100 to 500:100, and more preferably from 10:100 to 50:100. The liquid raw material is one or a mixture of coal tar, pitch, clarified oil, and ethylene tar, wherein the clarified oil is a catalytic slurry that has undergone simple treatment during catalytic cracking, with a saturated hydrocarbon and aromatic hydrocarbon content of 50%-60%. The heating process of the mixture of carbon nanotubes and liquid raw materials consists of three stages: 1) heating to 50-110°C for dehydration; 2) preheating the mixture of carbon nanotubes and liquid raw materials to 600-650°C and atomizing it into the reactor; 3) heating the mixture in the reactor to 1000°C-2300°C (optimal temperature is 1400-1700°C). Subsequently, water is sprayed in the quenching section to cool it to 800°C-860°C, and then cooled in three stages to 230°C-240°C. The mixture is then collected, dried at 70°C-120°C, and separated from the gaseous products. The resulting composite carbon filler has a particle size range of 50 nm to 500 μm. To verify its beneficial effects, compound rubbers containing different fillers were prepared using the same rubber formulation. The strength properties of the obtained rubber samples were compared, and the results showed that, under the same rubber formulation parameters, the tensile strength, elongation at break and other physical properties of the rubber with added composite fillers were significantly improved compared with the compound rubber using only N220 carbon black.
[0009] The drawback of the prototyping method is that without a tedious and time-consuming trial-and-error process to screen all possible proportions of the components, it is impossible to determine the optimal component ratio of the composite carbon filler. This exhaustive method is costly and cannot consistently yield the optimal content values of carbon nanotubes and carbon black in the rubber composition, making it difficult to guarantee that the final rubber and products have sufficiently excellent performance.
[0010] In summary, there is currently a lack of a method for preparing composite carbon fillers that can achieve both uniform compositing of carbon nanotubes and carbon black and directly determine the optimal ratio through calculation rather than trial and error. Summary of the Invention
[0011] In view of the problems mentioned in the background art regarding the preparation methods of existing composite carbon fillers, such as uneven dispersion of carbon nanotubes and carbon black, inability to directly determine the optimal ratio through calculation, and the need to rely on costly trial and error to screen components one by one, the present invention provides a method for preparing composite carbon fillers for rubber compositions.
[0012] This invention includes the following technical solutions: This invention provides a method for preparing a composite carbon filler for rubber compositions, comprising the following steps: S1: Determine the proportions and mix the precursors.
[0013] The mass ratio of carbon nanotubes to hydrocarbon raw materials is determined according to formula (I). Based on this mass ratio, the carbon nanotubes and hydrocarbon raw materials are loaded into a rotary hydrodynamic disperser and mixed using shear stress and cavitation to form a mixture. The temperature of the mixture is controlled to not exceed 60°C, and the mixing time is 2 to 20 minutes.
[0014] The mass ratio of the carbon nanotubes to the hydrocarbon feedstock is determined by the following formula (I): (I); in: -- The mass of carbon nanotubes, and its unit of mass is... Consistent; -- The quality of the hydrocarbon feedstock; -- Carbon black yield coefficient, , dimensionless, of which The mass of carbon black produced by pyrolysis; -- The ratio of raw rubber mass to carbon black mass in the rubber composition prepared according to the original formula. , dimensionless, of which For the quality of raw rubber, The mass of carbon black in the original formula; -- Specific surface area of carbon black, in m² 2 / g; -- Specific surface area of carbon nanotubes, in m² 2 / g; -- Average diameter of carbon nanotubes, in nm; -- Density of raw rubber, in g / cm³ 3 ; And in the formula (I) Under the above-mentioned unit system, it is a dimensionless number.
[0015] The reason this invention chooses a rotary hydrodynamic disperser as the mixing device, rather than conventional mechanical stirring or ultrasonic dispersion, is that this device can simultaneously provide two dispersion mechanisms: shear stress and cavitation. The rotary hydrodynamic disperser includes a rotor and a stator, both with flow channels on their sidewalls. The rotor speed is 3000 rpm, the working flow channel diameter is 0.1-0.2 m, the shear rate is 15.7-31.4 m / s, and the power is 6 kW. When the mixture of carbon nanotubes and hydrocarbon feedstock flows through the periodically opening and closing flow channel, it is subjected to the combined effects of turbulent pulsation, shear stress generated by the gap between the rotor and stator, strong pulse sound and hydrodynamic cavitation effect, and water hammer effect. Shear stress effectively breaks the van der Waals forces binding the carbon nanotube aggregates, while cavitation further peels and disperses the carbon nanotubes using the localized shock waves generated when bubbles collapse. The synergistic effect of these two mechanisms enables uniform dispersion of carbon nanotubes in the viscous liquid hydrocarbon feedstock, laying the foundation for subsequent in-situ composite processing.
[0016] During the above mixing process, the temperature of the mixture is controlled to not exceed 60°C. This is to prevent premature volatilization or localized thermal decomposition of the hydrocarbon feedstock during the mixing stage, thereby ensuring the quality and yield of the carbon black produced by subsequent pyrolysis.
[0017] The derivation of the above formula (I) is based on the following theoretical premises: First, to prepare high-quality, dense, and non-porous rubber materials, the rubber should fully wet all particles of the composite carbon filler, and form a rubber coating layer on the particle surface with a thickness of not less than twice the average diameter of the carbon nanotubes. Based on this premise, a quantitative relationship can be established between the amount of carbon nanotubes added and the coating capacity of the rubber matrix.
[0018] Second, in the rubber composition formulated according to the original recipe, the reduction in carbon black is directly proportional to the mass of carbon nanotubes added, with the ratio being the ratio of the specific surface areas of carbon black to those of carbon nanotubes. This is because the reinforcing effect of both carbon black and carbon nanotubes on rubber stems from their interfacial interaction with the rubber matrix. The larger the specific surface area, the greater the interfacial area provided by a unit mass of filler, and the smaller the required filler mass. This proportional relationship ensures that the total interfacial area of the composite filler is comparable to the interfacial area of carbon black in the original recipe, thus achieving an equivalent substitution in terms of reinforcing effect.
[0019] The carbon black yield coefficient in the above formula The following method is used to determine the degree of aromaticity of hydrocarbon feedstocks. This invention adopts well-known principles in carbon black production, using the Bureau of Mines Correlation Index (BMCI) to evaluate the aromaticity of the feedstock. The BMCI was established by the U.S. Bureau of Mines in 1940, and its calculation formula is a correlation index based on two fundamental properties of oil products: distillation range and density. The BMCI value uses n-hexane as 0 and benzene as 100 as benchmarks, and depends on the amount of aromatics in the hydrocarbon feedstock: if the hydrocarbon feedstock does not contain aromatics, the BMCI is 0; if it contains aromatics, the BMCI is greater than 0. The higher the aromatic content in the hydrocarbon feedstock used to prepare carbon black, the higher its BMCI. There is a positive correlation between the dispersion (particle specific surface area) of carbon black and BMCI: the higher the BMCI, the higher the specific surface area of the carbon black. An empirical relationship also exists between BMCI and carbon black yield, calculated separately for different grades of carbon black as follows: For N550 grade carbon black: Yield (%) = -0.0058 × (BMCI) 2 + 11.7331×(BMCI) - 64.4; For N220 grade carbon black: Yield (%) = -0.0023 × (BMCI) 2 + 0.7546×(BMCI) - 11.643.
[0020] For example, when the BMCI of the hydrocarbon feedstock used to prepare N550 grade carbon black is 127.5, substituting it into the corresponding formula yields a yield of 62.28%, i.e., the yield coefficient. Similar calculations can be used to obtain the yield coefficient of N220 grade carbon black. .
[0021] Therefore, formula (I) will convert the physical properties of the rubber matrix ( ), physical properties of carbon black ( ), physical properties of carbon nanotubes ( , ), original formula parameters ( ) and process parameters of hydrocarbon feedstock ( By incorporating them into a single quantitative model, the precise calculation of the ratio of carbon nanotubes to hydrocarbon raw materials is achieved, thus eliminating the need for trial-and-error screening to directly determine the optimal precursor ratio for composite carbon fillers.
[0022] S2: High-temperature pyrolysis in-situ generation of composite carbon filler.
[0023] The mixture obtained in step S1 is heated to 1400-1700°C to cause the hydrocarbon raw material to crack and generate carbon black, which forms a composite carbon filler with carbon nanotubes.
[0024] The heating is carried out in a vertical ultrasonic atomizing furnace. Specifically, the mixture obtained in step S1 is sprayed into a reaction furnace preheated to 1400-1700°C using an ultrasonic atomizer. The heating rate of the vertical ultrasonic atomizing furnace is: ≤10°C / min below 1400°C, and ≤5°C / min in the range of 1400°C to 1750°C.
[0025] Liquid hydrocarbon feedstock undergoes pyrolysis in a reactor to produce carbon black. The newly generated carbon black then combines in situ with carbon nanotubes already uniformly dispersed in the feedstock, forming a composite carbon filler in which carbon nanotubes are uniformly embedded in the carbon black matrix. This invention employs an in-situ pyrolysis method instead of physically mixing carbon nanotubes with pre-prepared carbon black because, during the pyrolysis of hydrocarbon feedstock to produce carbon black, carbon black particles nucleate and grow from the gas phase. Carbon nanotubes, as pre-existing solid-phase nucleation sites or dispersed phases, can be coated or anchored by the newly generated carbon black deposits, forming a strong interfacial bond. This in-situ generated composite structure exhibits stronger interfacial interactions compared to later physical mixing, which is beneficial for improving the mechanical properties of the final rubber composition.
[0026] The hydrocarbon feedstock is a liquid hydrocarbon feedstock used to produce ASTM D1765 standard N550 or N220 grade carbon black. The specific surface area of N550 grade carbon black is approximately 40-50 m². 2 / g, the specific surface area of N220 grade carbon black is approximately 110-130 m². 2 / g. The above raw materials have a mature production and application base in the carbon black industry, and their physical properties and pyrolysis behavior are well known to those skilled in the art.
[0027] S3: Collect composite carbon packing.
[0028] The product obtained in step S2 is cooled, and the composite carbon packing is collected using a water-cooled electrostatic filter. The water-cooled electrostatic filter is a cylindrical collection chamber with an annular electrode and a central electrode, and the electrostatic field voltage is 20-25 kV. After cooling, the high-temperature flue gas enters the electrostatic filter area. Under the action of the high-voltage electrostatic field, the composite carbon packing particles are ionized and directionally migrate to the surface of the collection electrode, achieving efficient separation from the gaseous products. The water-cooling system is used to control the temperature of the collection area, preventing structural changes or adhesion of the composite carbon packing due to overheating.
[0029] S4: Determine the amount of composite carbon filler used in the rubber composition.
[0030] The composite carbon filler collected in step S3 is introduced into the rubber composition, and the amount of composite carbon filler in the rubber composition is calculated by formula (II): (II); in: -- Content of composite carbon filler in rubber composition, in parts by weight, based on 100 parts of raw rubber; -- The ratio of raw rubber mass to carbon black mass in the rubber composition prepared according to the original formula, dimensionless; -- The carbon black content in the rubber composition prepared according to the original formula, in parts by weight, based on 100 parts of raw rubber; -- Specific surface area of carbon black, in m² 2 / g; -- Specific surface area of carbon nanotubes, in m² 2 / g; -- Average diameter of carbon nanotubes, in nm; -- Density of raw rubber, in g / cm³ 3 .
[0031] The derivation logic of Formula (II) is consistent with that of Formula (I). Based on the determined optimal input ratio of carbon nanotubes to hydrocarbon raw materials, Formula (II) further calculates the total amount of composite carbon filler used when 100 parts of raw rubber are used as a baseline. The core idea is that the carbon black portion of the composite carbon filler replaces the carbon black in the original formulation, while the carbon nanotube portion is introduced as a reinforcing additive. The combined effect of both adjusts the total amount of composite filler relative to the original carbon black content. This formula ensures that the total interfacial area of the composite filler matches the interfacial area of the carbon black in the original formulation, thereby achieving an equivalent or even superior reinforcing effect.
[0032] Compared with the prior art, the present invention has the following beneficial effects: (1) Precisely determine the optimal ratio and eliminate trial-and-error dependence. This invention realizes the precise calculation of the input ratio of carbon nanotubes to hydrocarbon raw materials and the amount of composite carbon filler in rubber composition through formula (I) and formula (II). For any rubber grade, the optimal ratio can be obtained directly by simply substituting its physical property parameters into the formula, without the need for a large number of ratio screening tests, which significantly reduces the research and development cost and time consumption.
[0033] (2) In-situ composite achieves uniform dispersion and strong interfacial bonding. In this invention, carbon nanotubes are first uniformly dispersed in liquid hydrocarbon raw materials, and then carbon black is generated in-situ through the cracking of the hydrocarbon raw materials. The newly generated carbon black is deposited and grown on the surface of the carbon nanotubes to form a composite structure of carbon black coating carbon nanotubes. Compared with the existing method of preparing carbon black and carbon nanotubes separately and then physically mixing them, this invention avoids the problems of carbon nanotube agglomerates being compacted and unevenly dispersed in physical mixing, and achieves uniform distribution and strong interfacial bonding of carbon nanotubes in the carbon black matrix.
[0034] (3) Significantly improved mechanical properties. After introducing the composite carbon filler prepared in this invention into the rubber composition according to the optimal dosage calculated by formula (II), all mechanical properties are significantly improved. Experimental data prove that the method described in this invention can effectively improve the comprehensive mechanical properties of the rubber composition. In the applicant's previous research, the composite filler prepared by the in-situ composite method consistent with the process principle of this invention, under the condition of a total filler addition of 18 phr, increased the tensile strength of rubber by 3.0 MPa, the elongation at break by 15%, the stress at 100% elongation by 0.2 MPa, and the Shore hardness by 3 degrees compared with the stepwise feeding method, further verifying the advantages of the in-situ composite process over the stepwise feeding method in improving the mechanical properties of rubber.
[0035] (4) Significant cost advantage. The carbon nanotube content in the composite carbon filler prepared by this invention is much lower than that of the prototype scheme. This means that while obtaining better mechanical properties, the amount of expensive raw material carbon nanotubes used is greatly reduced, and the product cost is significantly lower than that of the existing technology.
[0036] (5) High efficiency and low energy consumption. The mixing time in the rotary fluid dynamic disperser of the present invention is only 2 to 20 minutes, and the temperature of the mixture is controlled at no more than 60°C. Compared with the long ultrasonic treatment or high energy consumption drying process in the prior art, the mixing efficiency of the present invention is higher and the energy consumption is lower.
[0037] (6) Simple to operate and suitable for industrial application. The method described in this invention only requires minor modifications to conventional standard equipment for industrial application. The rotary fluid dynamic disperser, vertical ultrasonic atomizing furnace and water-cooled electrofiltration unit involved are all mature industrial equipment, and there is no need to develop special equipment. It has good industrial feasibility and economy. Attached Figure Description
[0038] Figure 1: Rotary fluid dynamic disperser: a—Photo of laboratory equipment; b—Drawing of flow components: 1—Stator, 2—Rotor, 3—Gasket for adjusting the gap between the stator and rotor disc, 4—End face seal; c—Working components: 1—Rotor disc, 2—Stator disc; Figure 2: Figure 2 a is a SEM image of the composite carbon filler prepared using an in-situ composite process consistent with the process principle of this invention; Figure 2 b is an SEM image of the composite carbon filler prepared by the physical mixing method. Detailed Implementation
[0039] I. Raw Materials and Equipment The present invention will be further described in detail below with reference to the embodiments, but the implementation of the present invention is not limited thereto.
[0040] 1. Main raw materials The main raw materials used in the various embodiments of this invention are as follows: Liquid hydrocarbon feedstock (specific surface area) used for the production of ASTM D1765 standard N550 grade carbon black. m 2 / g); Liquid hydrocarbon feedstock (specific surface area) used for the production of ASTM D1765 standard N220 grade carbon black. m 2 / g); Carbon nanotubes (compliant with TU 24.1-03291669-009:2009 technical specifications, specific surface area) m 2 / g, average diameter nm); Nitrile butadiene rubber (NBR) 3365 (raw rubber density) g / cm 3 ); Natural rubber SMR 20 (raw rubber density) g / cm 3 ); Industrial zinc oxide (sulfide activator); ASTM Standard 1801 Stearic Acid; ASTM standard antioxidant IPPD (N-isopropyl-N'-phenyl-p-phenylenediamine); ASTM standard mold release agent 935P; DOP plasticizer (dioctyl phthalate); Sulfur powder (98.5% purity, Sigma-Aldrich); Accelerator CBS (N-cyclohexyl-2-benzothiazole sulfenamide); Accelerator TMTD (tetramethylthiuram disulfide).
[0041] 2. Main Equipment The main equipment used in the various embodiments of the present invention is as follows: Rotary hydrodynamic disperser: such as Figure 1As shown in a-1c, the rotary fluid dynamic disperser used in this invention is the model described in patent No. 97623. Figure 1 a is a photograph of the actual device. Figure 1 b is a schematic diagram of the flow-through components of the equipment (1—stator, 2—rotor, 3—shims used to adjust the gap between the stator and rotor discs, 4—end face seal). Figure 1 c is a detailed schematic diagram of the working components of the equipment (1—rotor disc, 2—stator disc). The core components of the equipment are the rotor and stator, both of which have flow channels on their side walls. The rotor speed is 3000 rpm, the working flow channel diameter is 0.1-0.2 m, the shear rate is 15.7-31.4 m / s, and the power is 6 kW. The medium to be treated flows through the periodically opening and closing flow channels and is then discharged from the equipment. During the treatment process, the medium is subjected to the combined effects of various factors, including turbulent pulsation, mechanical action of structural components, shear stress generated by the gap between the rotor and stator, strong pulse sound and hydrodynamic cavitation effect, and water hammer effect.
[0042] Vertical ultrasonic atomizing furnace: OTF-1750X-VT model manufactured by Hefei Kejing Materials Technology Co., Ltd. Power supply specifications: 380V AC, 50 / 60Hz, maximum power 15kW. Long-term operating temperature: 1700℃, total heating zone length: 800mm. Heating rate: ≤10℃ / min below 1400℃, ≤5℃ / min between 1400℃ and 1750℃. Temperature control uses type B double platinum-rhodium thermocouple. Average droplet size of atomized liquid is 1–5 micrometers.
[0043] Water-cooled electrofiltration unit: A cylindrical collection chamber with annular electrodes and a central electrode, used in conjunction with the OTF-1750X-VT vertical ultrasonic atomizing furnace, with an electrostatic field voltage of 20-25kV.
[0044] Z-type Banbury internal mixer: used for mixing rubber compositions.
[0045] Bridge two-roll open mill: used for supplementary mixing of rubber compositions.
[0046] Hot press: used for vulcanization molding of rubber compositions.
[0047] 2167 P50 Tensile Testing Machine: Used for mechanical property testing.
[0048] Testometric MT350 tensile testing machine: used for mechanical property testing.
[0049] MOM Q1500D Integrated Thermal Analyzer: Used for thermogravimetric analysis of carbon nanotube content in composite carbon fillers.
[0050] 3. Original rubber composition formulation To verify the technical effect of the present invention, rubber compositions based on nitrile rubber NBR 3365 and natural rubber SMR 20 were prepared according to the following original formulations.
[0051] Table 1 Original Formulation – Rubber Compositions Based on Nitrile Butadiene Rubber NBR 3365 (Unit: Parts by Mass) Table 2 Original Formulation – Rubber Compositions Based on Natural Rubber SMR 20 (Parts by Mass) Example 1: Step 1: Calculate the mass ratio of carbon nanotubes to hydrocarbon feedstock.
[0052] For the rubber composition based on nitrile butadiene rubber (NBR 3365) prepared according to the original formulation in Table 1, its raw rubber density is... g / cm 3 The carbon black content in the original formula Parts by weight (based on 100 parts of raw rubber), the ratio of raw rubber mass to carbon black mass. The hydrocarbon feedstock used is a liquid hydrocarbon feedstock for producing ASTM D1765 standard N550 grade carbon black, and its carbon black yield coefficient is... specific surface area of carbon black m 2 / g. Specific surface area of the carbon nanotubes used. m 2 / g, average diameter nm.
[0053] Substitute the above parameters into formula (I): ; After substituting the parameters, the calculation yields: ; Step 2: Mix the precursors.
[0054] 5000 grams of liquid hydrocarbon raw material for preparing N550 grade carbon black was loaded into a rotary hydrodynamic disperser, and 50 grams of carbon nanotubes (by mass ratio) were added. Stir for 8 minutes while continuously monitoring the temperature of the mixture. After 8 minutes, when the temperature of the mixture reaches 60°C, stop stirring and pour out the mixture.
[0055] Step 3: High-temperature pyrolysis in situ generates composite carbon filler.
[0056] The mixture obtained in step 2 is sprayed into an OTF-1750X-VT vertical ultrasonic atomizing furnace preheated to 1500°C using an ultrasonic atomizer. The liquid hydrocarbon feedstock undergoes cracking in the reactor to generate carbon black, which combines in situ with the carbon nanotubes that are already uniformly dispersed in the feedstock to form a composite carbon filler.
[0057] Step 4: Collect the composite carbon filler.
[0058] The reaction product was cooled and then fed into a water-cooled electrofiltration unit, where the composite carbon filler was collected under a 20-25 kV electrostatic field. The total mass of the obtained composite carbon filler was 3150 g. Thermogravimetric analysis using a MOM Q1500D integrated thermal analyzer determined the carbon nanotube content in the composite carbon filler to be 1.6 wt%.
[0059] Step 5: Calculate the amount of composite carbon filler used in the rubber composition.
[0060] The composite carbon filler collected in step 4 is introduced into the nitrile rubber NBR 3365-based rubber composition of the original formulation in Table 1, and the amount of composite carbon filler is calculated according to formula (II) (based on 100 parts of raw rubber).
[0061] Formula (II): ; Substitute the following parameters into the above formula: weight, , g / cm 3 , m 2 / g, m 2 / g, nm.
[0062] The calculation yields: ; Step 6: Prepare the rubber composition and test its properties.
[0063] Add 1000 g of NBR 3365 nitrile rubber (10 times the calculated standard dosage of 100 parts) to a Z-type Banbury internal mixer and mix for 4 minutes. Simultaneously add 50 g of industrial zinc oxide, 15 g of stearic acid, 20 g of antioxidant IPPD, and 10 g of mold release agent 935P. Then add 810.4 g of the composite carbon filler prepared in step 4 (i.e., 81.04 × 10⁻⁶) and 100 g of DOP plasticizer, and continue mixing for 5 minutes. Pour out the resulting mixture and cool it to below 110°C. Then, add 15 g of accelerator CBS and 20 g of accelerator TMTD to a Bridge two-roll mill and mix for 5 minutes until homogeneous. Let the resulting mixture stand at room temperature for 12 hours, then vulcanize it in a hot press at 150°C and 15 MPa using a special mold to obtain samples for mechanical property testing.
[0064] The mechanical properties of the samples were determined according to ASTM standard test methods: tensile strength, elongation at break, stress at 100% elongation, tear strength, and Shore hardness were measured using a 2167 P50 tensile testing machine and a Testometric MT350 tensile testing machine. The results are as follows: Tensile strength: 18.8 MPa Elongation at break: 374% 100% constant tensile stress: 10.5 MPa Tear strength: 84.6 kN / m Shore hardness: 76.
[0065] Example 2: Step 1: Calculate the mass ratio of carbon nanotubes to hydrocarbon feedstock.
[0066] For the rubber composition based on natural rubber SMR 20 prepared according to the original formulation in Table 2, its raw rubber density is... g / cm 3 The carbon black content in the original formula Parts by weight (based on 100 parts of raw rubber), the ratio of raw rubber mass to carbon black mass. The hydrocarbon feedstock used is a liquid hydrocarbon feedstock for producing ASTM D1765 standard N220 grade carbon black, and its carbon black yield coefficient is... specific surface area of carbon black m 2 / g. Specific surface area of the carbon nanotubes used. m 2 / g, average diameter nm.
[0067] Substitute the above parameters into formula (I): ; After substituting the parameters, the calculation yields: ; Step 2: Mix the precursors.
[0068] 5000g of liquid hydrocarbon raw material for preparing N220 grade carbon black was loaded into a rotary hydrodynamic disperser, and 125g of carbon nanotubes (by mass ratio) were added. Stir for 4 minutes while continuously monitoring the temperature of the mixture. After 4 minutes, when the temperature of the mixture reaches 60°C, stop stirring and pour out the mixture.
[0069] Step 3: High-temperature pyrolysis in situ generates composite carbon filler.
[0070] The mixture obtained in step 2 is sprayed into an OTF-1750X-VT vertical ultrasonic atomizing furnace preheated to 1700°C using an ultrasonic atomizer. The liquid hydrocarbon feedstock undergoes cracking in the reactor to generate carbon black, which combines in situ with the carbon nanotubes that are already uniformly dispersed in the feedstock to form a composite carbon filler.
[0071] Step 4: Collect the composite carbon filler.
[0072] The reaction product was cooled and then fed into a water-cooled electrofiltration unit, where the composite carbon filler was collected under a 20-25 kV electrostatic field. The total mass of the obtained composite carbon filler was 2475 g. Thermogravimetric analysis revealed that the carbon nanotube content in the composite carbon filler was 5.0 wt%.
[0073] Step 5: Calculate the amount of composite carbon filler used in the rubber composition.
[0074] The composite carbon filler collected in step 4 is introduced into the natural rubber SMR 20-based rubber composition of the original formulation in Table 2, and the amount of composite carbon filler is calculated according to formula (II) (based on 100 parts of raw rubber).
[0075] Formula (II): ; Substitute the following parameters into the above formula: weight, , g / cm 3 , m 2 / g, m 2 / g, nm.
[0076] The calculation yields: ; Step 6: Prepare the rubber composition and test its properties.
[0077] The rubber composition was prepared using the same method as in step 6 of Example 1, except that 1000 grams of natural rubber SMR 20 was used, and 307.8 grams of the composite carbon filler prepared in step 4 (i.e., 30.78 × 10⁻⁶) were added. The antioxidant IPPD, mold release agent 935P, DOP plasticizer, and accelerator TMTD were not added (according to the original formulation in Table 2). The mixing, vulcanization, and testing methods were the same as in Example 1.
[0078] The mechanical property test results are as follows: Tensile strength: 23.9 MPa Elongation at break: 984% 100% constant tensile stress: 3.3 MPa Tear strength: 107.6 kN / m Shore hardness: 61.2.
[0079] Table 3 Summary of parameters and calculation results for each embodiment Comparative Example 1: Comparison with the original formula of Example 1.
[0080] For comparison, a carbon nanotube-free NBR 3365-based rubber composition was prepared according to the original formulation in Table 1. The specific steps are as follows: 1000 g of NBR 3365 nitrile rubber was added to a Z-type Banbury internal mixer and mixed for 4 minutes, while simultaneously adding 50 g of industrial zinc oxide, 15 g of stearic acid, 20 g of antioxidant IPPD, and 10 g of mold release agent 935P. Then, 800 g of carbon black N550 and 100 g of DOP plasticizer were added, and mixing continued for 5 minutes. The resulting mixture was poured out and cooled to below 110°C. Subsequently, 15 g of accelerator CBS and 20 g of accelerator TMTD were added to a Bridge two-roll mill and mixed for 5 minutes until homogeneous. The resulting mixture was allowed to stand at room temperature for 12 hours, followed by vulcanization in a hot press at 150°C and 15 MPa. Mechanical properties were determined according to the same test methods as in Example 1.
[0081] The mechanical property test results are as follows: Tensile strength: 16.6 MPa Elongation at break: 220% 100% constant tensile stress: 8.2 MPa Tear resistance: 67.2 kN / m Shore hardness: 76.
[0082] Comparative Example 2: Comparison with the original formula of Example 2.
[0083] For comparison, a natural rubber SMR 20-based rubber composition without carbon nanotubes was prepared according to the original formulation in Table 2. The specific steps are as follows: 1000 g of natural rubber SMR 20 was added to a Z-type Banbury mixer and mixed for 4 minutes, while simultaneously adding 30 g of industrial zinc oxide and 10 g of stearic acid. Then, 300 g of carbon black N220 was added, and mixing continued for 5 minutes. The resulting mixture was poured out and cooled to below 110°C. Subsequently, 17 g of sulfur powder and 25 g of accelerator CBS were added to a Bridge two-roll mill and mixed for 5 minutes until homogeneous. The resulting mixture was allowed to stand at room temperature for 12 hours, followed by vulcanization in a hot press at 150°C and 15 MPa. Mechanical properties were determined according to the same test methods as in Example 1.
[0084] The mechanical property test results are as follows: Tensile strength: 20.4 MPa Elongation at break: 874% 100% constant tensile stress: 2.7 MPa Tear strength: 81.6 kN / m Shore hardness: 59.
[0085] Test example: 1. Testing Methods The mechanical properties of the rubber composition samples prepared in the above embodiments and comparative examples were determined according to the following test standards and methods: Tensile strength: Determined according to ASTM D412 standard using a 2167 P50 tensile testing machine or a Testometric MT350 tensile testing machine. The specimen is dumbbell-shaped, and the tensile rate is 500 mm / min.
[0086] Elongation at break: Measured simultaneously with tensile strength, the elongation at the point of fracture of the specimen is recorded.
[0087] 100% elongation stress: Record the stress value when the specimen is stretched to 100% elongation according to ASTM D412 standard.
[0088] Tear resistance: determined using trouser-shaped specimens in accordance with ASTM D624 standard.
[0089] Shore hardness: Measured using a Type A hardness tester according to ASTM D2240 standard.
[0090] 2. Determination of carbon nanotube content in composite carbon fillers The content of carbon nanotubes in the composite carbon fillers obtained in each example was determined by thermogravimetric analysis (TGA) using a MOM Q1500D integrated thermal analyzer. Test conditions: air atmosphere, heating rate 10°C / min, from room temperature to 800°C. Carbon black completely oxidizes and decomposes at approximately 500-600°C, and carbon nanotubes completely oxidize and decompose at approximately 600-700°C. The carbon nanotube content was calculated based on the weight loss steps on the thermogravimetric curves.
[0091] 3. Performance Comparison Results Table 4 Comparison of mechanical properties of each embodiment and comparative example Table 5. Strength performance improvement of each embodiment of the present invention relative to the comparative example (original formula) 4. Comparison with the prototype design The relative improvement in carbon nanotube content and rubber composition strength properties in the composite carbon filler of Examples 1 and 2 of the present invention is compared with that of the closest prior art (prototype CN108047495B). The results are shown in Table 6. The prototype data are from the examples and comparative examples in the specification of CN108047495B.
[0092] Table 6 Performance Comparison of the Invention and the Prototype Solution (CN108047495B) 5. Comparison with the step-by-step feeding method To verify the advantages of in-situ composite technology over stepwise feeding in terms of reinforcement effect, the applicant conducted a comparative experiment. A composite filler sample (sample S5) was prepared using an in-situ composite method consistent with the principle of this invention, while a control sample (sample S8) was prepared using a stepwise feeding method. The total filler addition amount for both was 18 phr, and the rubber matrix was nitrile rubber (NBR 3365). The mechanical property test results are shown in Table 7.
[0093] Table 7 Performance Comparison of In-situ Composite and Stepwise Feeding (Total Filler Addition Amount: 18 phr) Note: In-situ composite sample S5 is a composite filler (filler system is CB-CNT-PS) prepared using an in-situ composite method consistent with the process principle of this invention; control sample S8 is a rubber composition prepared by stepwise addition of fumed silica and carbon nanotubes. Both samples use NBR 3365 as the rubber matrix, and the total filler addition is 18 phr. The above data are from the applicant's internal comparative experiments. The data in this table differs slightly from the filler system in the embodiments of this invention (the former contains fumed silica PS), but they share the same guiding principle that "in-situ composite is superior to stepwise addition."
[0094] Table 7 shows that, under the same total filler addition, the composite filler prepared by the in-situ compounding process, compared with the stepwise feeding method, exhibits a 3.0 MPa increase in tensile strength, a 15% increase in elongation at break, a 0.2 MPa increase in stress at 100% elongation, and a 3-degree increase in Shore hardness. These results further validate the advantages of the in-situ compounding process over the stepwise feeding method in improving the mechanical properties of rubber.
[0095] 6. Results Analysis The test results in Tables 4 to 7 show that: (1) Compared with the original formulations (Comparative Examples 1 and 2), the composite carbon filler prepared by the method of the present invention can significantly improve the various mechanical properties of the rubber composition. Specifically, for the NBR 3365 nitrile rubber-based composition, the tensile strength is increased by 13.2%, the elongation at break is increased by 70.0%, the stress at 100% elongation is increased by 28.0%, and the tear strength is increased by 25.9%; for the natural rubber SMR 20-based composition, the tensile strength is increased by 15.0%, the elongation at break is increased by 12.6%, the stress at 100% elongation is increased by 22.2%, and the tear strength is increased by 31.8%.
[0096] (2) Compared with the prototype scheme (CN108047495B), the present invention achieves a better mechanical property improvement effect while significantly reducing the amount of carbon nanotubes used. The carbon nanotube content of Example 1 (1.6 wt%) is only about 1 / 13 of that of the prototype scheme (21.0 wt%), but the increase in tensile strength (13.2%) is higher than that of the prototype scheme (10.8%), and the increase in tear strength (25.9%) is also higher than that of the prototype scheme (24.5%). The carbon nanotube content of Example 2 (5.0 wt%) is about 1 / 4 of that of the prototype scheme, and the increase in tensile strength (15.0%) is significantly higher than that of the prototype scheme (10.8%), and the increase in tear strength (31.8%) is also significantly higher than that of the prototype scheme (24.5%). This shows that the present invention achieves a better reinforcement effect with a much lower amount of carbon nanotubes used than the prior art by accurately calculating the optimal ratio by formula and combining it with in-situ composite process, which has significant cost advantages and technological progress.
[0097] (3) The results of Examples 1 and 2 show that the formulas (I) and (II) provided by the present invention have good applicability to different rubber grades (nitrile rubber and natural rubber) and different carbon black grades (N550 and N220), proving that the present invention has universality and industrial application value.
[0098] 7. Microscopic morphological characterization To visually verify the effect of the in-situ composite method described in this invention on improving the dispersion uniformity of carbon nanotubes, the applicant provided scanning electron microscope (SEM) images of composite carbon fillers prepared using an in-situ composite process consistent with the process principle of this invention, as well as SEM images of a control sample of composite carbon fillers prepared using a physical mixing method.
[0099] like Figure 2 As shown in Figure a, in the composite carbon filler prepared by the in-situ composite process, carbon nanotubes are uniformly embedded in the carbon black matrix, and no obvious carbon nanotube aggregates were observed. The interface between the carbon black particles and the carbon nanotubes is tightly bonded, with no peeling or voids observed, indicating that the newly generated carbon black during the in-situ composite process is deposited and grown on the surface of the carbon nanotubes, forming a robust composite structure.
[0100] like Figure 2 As shown in b, in the control sample of composite carbon filler prepared by the physical mixing method, carbon nanotubes are distributed in an aggregated state on the surface of carbon black particles, with a large number of carbon nanotube aggregates with a size of micrometer. There is no effective interfacial bonding between carbon black particles and carbon nanotubes; the two coexist only through physical contact.
[0101] The above comparison of microstructures shows that the in-situ composite process enables carbon nanotubes to be uniformly dispersed in the carbon black matrix, avoiding the problems of compaction and uneven dispersion of carbon nanotube aggregates in physical mixing methods. This provides a structural basis for improving the mechanical properties of the rubber composition. These microscopic observations corroborate the macroscopic mechanical property test data in Tables 4 to 6, jointly confirming the effectiveness of the technical solution described in this invention.
[0102] It should be noted that the above embodiments are merely preferred embodiments of the present invention, used to explain the technical principles and application effects of the present invention, and are not intended to limit the scope of protection of the present invention. Any equivalent substitutions, modifications, or improvements made based on the technical concept of the present invention within the spirit and principles of the present invention should be included within the scope of protection of the present invention. In practical applications, those skilled in the art can make adaptive adjustments to the relevant parameters according to the specific test materials, working conditions, and accuracy requirements, all of which fall within the scope of protection of the present invention.
Claims
1. A method for preparing a composite carbon filler for rubber compositions, characterized in that, Includes the following steps: S1: Determine the mass ratio of carbon nanotubes to hydrocarbon raw materials according to formula (I), and load the carbon nanotubes and hydrocarbon raw materials into a rotary fluid dynamic disperser according to the mass ratio. Mix them by utilizing shear stress and cavitation to form a mixture, and control the temperature of the mixture. S2: The mixture is heated to 1400-1700°C to cause the hydrocarbon raw material to crack and generate carbon black, and the carbon black and carbon nanotubes form a composite carbon filler. S3: Cool the product obtained in step S2 and collect the composite carbon filler using a water-cooled electrofiltration device; (I); in: -- The mass of carbon nanotubes, and its unit of mass is... Consistent; -- The quality of the hydrocarbon feedstock; -- Carbon black yield coefficient, , dimensionless, of which The mass of carbon black produced by pyrolysis; -- The ratio of raw rubber mass to carbon black mass in the rubber composition prepared according to the original formula. , dimensionless, of which For the quality of raw rubber, The mass of carbon black in the original formula; -- Specific surface area of carbon black, in m² 2 / g; -- Specific surface area of carbon nanotubes, in m² 2 / g; -- Average diameter of carbon nanotubes, in nm; -- Density of raw rubber, in g / cm³ 3 ; And in the formula (I) Under the above-mentioned unit system, it is a dimensionless number.
2. The method according to claim 1, characterized in that, In step S1, the temperature of the mixture is controlled to be no more than 60°C.
3. The method according to claim 1 or 2, characterized in that, In step S1, the mixing time is 2 to 20 minutes.
4. The method according to claim 1, characterized in that, In step S1, the rotary fluid dynamic disperser includes a rotor and a stator. The sidewalls of the rotor and the stator are provided with flow channels. The rotor speed is 3000 rpm, the working flow channel diameter is 0.1-0.2 m, the shear rate is 15.7-31.4 m / s, and the power is 6 kW.
5. The method according to claim 1, characterized in that, In step S2, the heating is carried out in a vertical ultrasonic atomizing furnace, and the heating rate of the vertical ultrasonic atomizing furnace is: ≤10°C / min below 1400°C, and ≤5°C / min in the range of 1400°C to 1750°C.
6. The method according to claim 1, characterized in that, In step S2, the mixture obtained in step S1 is sprayed into a reaction furnace preheated to 1400-1700°C using an ultrasonic atomizer. The liquid hydrocarbon raw material is cracked in the reaction furnace to generate carbon black, which forms a composite carbon filler with the carbon nanotubes.
7. The method according to claim 1, characterized in that, In step S3, the water-cooled electrofilter is a cylindrical collecting cavity with an annular electrode and a central electrode, and the electrostatic field voltage is 20-25 kV.
8. The method according to claim 1, characterized in that, The method further includes step S4: introducing the composite carbon filler collected in step S3 into the rubber composition, wherein the amount of composite carbon filler in the rubber composition is calculated by formula (II): (II); in: -- Content of composite carbon filler in rubber composition, in parts by weight, based on 100 parts of raw rubber; -- The ratio of raw rubber mass to carbon black mass in the rubber composition prepared according to the original formula, dimensionless; -- The carbon black content in the rubber composition prepared according to the original formula, in parts by weight, based on 100 parts of raw rubber; -- Specific surface area of carbon black, in m² 2 / g; -- Specific surface area of carbon nanotubes, in m² 2 / g; -- Average diameter of carbon nanotubes, in nm; -- Density of raw rubber, in g / cm³ 3 .
9. The method according to claim 1, characterized in that, The hydrocarbon feedstock is a liquid hydrocarbon feedstock used to produce ASTM D1765 standard N550 or N220 grade carbon black.
10. The method according to claim 1, characterized in that, The carbon black yield coefficient Determined by the following empirical formula: For N550 grade carbon black: Yield (%) = -0.0058 × (BMCI) 2 + 11.7331×(BMCI) - 64.4; For N220 grade carbon black: Yield (%) = -0.0023 × (BMCI) 2 + 0.7546×(BMCI) - 11.643; Wherein BMCI is the aromatics correlation index of the hydrocarbon feedstock, which is dimensionless.
Citation Information
Patent Citations
An in-situ preparation method of a super-strong composite filler of carbon nanotubes and carbon black
CN108047495B
Carbon nanostructure preblends and their applications
US20190322818A1